Landslide issues in Penang, Malaysia:students’ environmental knowledge, attitude and practice - Habibah Lateh,; Jamilah Ahmad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
This paper presents the findings of a field survey of supposedly educated young Malaysians regarding their knowledge of landslide as an environmental hazard and their attitudes and practice regarding landslide issues. The respondents were undergraduate students of Penang’s Universiti Sains Malaysia whose RST (Restu, Saujana, Tekun) residential hostels were chosen for the study due to their location on a mountainous terrain. A total of 343 students participated in the survey. The results indicated that most of the students did have the general knowledge on landslides. They understood the nature of landslide hazards and how they occur. Nevertheless many had not attended any seminars on landslide issues and some were still in the dark about this hazard.